Administrative monetary penalties in the amendment to the data protection law – solutions on the background of the polish law and the European Union law - Szelągowska, Karolina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The problem of this scientific article focus on the issue of administrative monetary penalties. The literature recognizes the increasing use of administrative monetary penalties by public administration bodies. Considering that, the effectiveness of this means the legislator more often decides to place regulations constituting administrative monetary penalties in subsequent substantive law acts. The practice of public administration bodies also shows that these bodies very often use administrative monetary penalties as a consequense of a breach of the law by failure to perform a legal duty or violation of prohibition. This research discus the basic assumptions and objectives of administrative monetary penalties in the data protection law, and then describes the procedure for imposing them. The theoretical layer was enriched by, among others first practical experience and de lege ferenda postulates.